On the correlation of “enterprise” and “common immovable complex” categories - F. K. Turdimatov (Russian Journal of Economics and Law)
Objective: to analyze and compare the legal categories “enterprise” and “common immovable complex” as “complex” objects of civil rights in the comparative aspect. Methods: the formal-logical and comparative methods of research. Results: The general and specific characteristics of an enterprise and a single real estate complex are revealed. The author gives a definition of the legal category “enterprise” and concludes that the applying the real estate legal regime to these complex objects is the simplification of their civil circulation. Scientific novelty: The author distinguishes the criteria for distinguishing such categories as “enterprise” and “common immovable complex”. Practical value: The results of scientific research can be used in law-making and practical activities, as well as for scientific research in the sphere of civil law.